'Policies that Fail – Words that Succeed': The Politics of Accessible Housing in Australia. Issue 1 (8th August 2016) - Ward, Margaret; Jacobs, Keith
Abstract : This paper seeks to contribute to the debate over the efficacy of voluntary agreements versus regulation, and uses a study of the Livable Housing Design initiative to deliver voluntarily new‐built accessible housing in Australia. We first probe why regulation has become such a significant component of government policy making, and then ask why political campaigns focus on this issue as a strategy for reform. We refer to research by disability activists, which claims that the voluntary approach has failed and regulation is necessary. Amongst our conclusions are: (1) that the disjuncture between policy rhetoric and outcome can be attributed to the power of lobbyists, reliance on the private market to address inequality, and antipathy to regulatory enforcement; and (2) that there is a need for greater interrogation of the language deployed in policy texts to identify whether they are crafted to maintain the government's legitimacy or to deliver purposeful change. Abstract : The paper considers the disjuncture between government policy rhetoric to increase the supply of accessible housing and outcomes. Government failure can be sourced to the hegemony of private market ideology and aversion to regulation. A purposeful and incisive critique of government policymaking is the first step to effective interventions